Influence of the cast blank manufacturing accuracy on the number of steps and labor input into its machining - Dusaniuk, Zh. P.; Deribo, O. V.; Morhun, I. D. (Visnyk of Vinnytsia Politechnical Institute, 2015)
Comparative study of the expediency of widely-used methods application for manufacturing primary cast blank of the part is carried out in order to provide the required accuracy of the most important surfaces in terms of reducing labor input into their further machining.